Numerical methods for changing type systems. (23rd June 2018) - Franz, Sebastian; Trostorff, Sascha; Waurick, Marcus
Abstract: In this paper we develop a numerical method for partial differential equations with changing type. Our method is based on a unified solution theory found by Rainer Picard for several linear equations from mathematical physics. Parallel to the solution theory already developed, we frame our numerical method in a discontinuous Galerkin approach in time with certain exponentially weighted spaces combined with a finite element method in space.